Growth and Yield of Mustard (Brassica juncea L.) in Nagpur Mandarin-based Agroforestry System in South-Eastern Rajasthan - Bhupendra Singh; S. B. S. Pandey; Aditya Kumar Jayant (Annals of Agricultural Research, 2023)
The field experiment was conducted during 2020-21 and 2021-22 at the Instructional Farm, Department of Fruit Science, College of Horticulture and Forestry, Jhalawar (Agriculture University, Kota). The fourteen year old plantation of Nagpur mandarin (Citrus reticulata Blanco.) was used for the present intercropping study. The mustard crop (Brassica juncea L.) with three varieties (Giriraj, RH-725 and NRCHB-101) was selected along with two biofertilizers (Azotobacter and PSB) for the study. The experiment was laid out a randomized block design with twenty four treatments and three replications. The observation on growth and yield were recorded during the course of investigation under study for both the years. At the harvesting stage, maximum plant height, fresh and dry weight of plant, number of pods per plant, seeds per pod and 1000 seed’s weight of mustard was registered under mandarin based agroforestry system as compared to their sole cropping system. During both year of study, the maximum seed yield, biological yield and oil yield was found maximum in sole cropping system (17.49 m2 ) due to small plot size comparison to intercropping (36 m2 ).